The Influence of Marketing Factors on Repurchase Intention of Imported Halal Products in Border Areas Between Countries: The Case of Batam City - Noval Christanto; Immanuel Zai (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid growth of the halal market has increased consumer attention toward imported halal food products, particularly in terms of trust and repeat purchasing behavior. However, differences in country of origin and information asymmetry often raise concerns regarding product reliability, making trust a critical issue in influencing consumers’ repurchase intention. This study addresses the problem of identifying key factors that build consumer trust and how such trust affects repurchase intention toward imported halal products in Batam City. Accordingly, this study aims to analyze the influence of brand image, product quality, halal certification, perceived value, and electronic word of mouth (E-WOM) on trust, as well as the effect of trust on repurchase intention. A quantitative research approach was employed by distributing online and offline questionnaires to 357 respondents aged 17–50 years in Batam City who had previously purchased imported halal food products. The collected data were analyzed using Structural Equation Modelling (SEM) with the SmartPLS application. The results indicate that brand image, product quality, halal certification, perceived value, and E-WOM have a significant positive effect on trust. Furthermore, trust has a significant positive influence on repurchase intention and serves as a mediating variable in the relationship between these antecedent factors and repurchase intention. These findings highlight the central role of trust in shaping consumer loyalty toward imported halal products and provide valuable insights for both academics and practitioners in the halal marketing field.